The role of mentoring in developing leaders’ emotional intelligence: exploring mentoring types, emotional intelligence, organizational factors, and gender - Prummer, Katharina; Human-Vogel, Salomé; Graham, Marien Alet; Pittich, Daniel (Frontiers in Education, 2024)
Emotional awareness, emotional regulation, empathy, and resilience are key components of emotional intelligence. Twenty-first-century leaders require such competencies, and prior research establishes a positive impact of emotional intelligence on leadership and well-being. The mechanisms through which leaders develop these competencies remain unclear. Mentoring, a developmental tool linked with well-being, has not been extensively studied for its role in emotional intelligence development. The current study investigates this relationship within the context of vocational education and training in South Africa. The mentoring framework includes individual, peer group, and key performance area mentoring. In previous research on this mentoring framework, leaders perceived emotional well-being as the most important outcome of mentoring and development, constituting another vital factor. Data were collected from a treatment group of leaders who have participated in the mentoring framework and a control group of leaders and lecturers (N = 139). The present study uses exploratory and confirmatory factor analysis to validate the Schutte Self-Report Emotional Intelligence Test within this context. In the next step, we employed descriptive analysis to answer which mentoring type was best perceived to support emotional intelligence. Using the Mann-Whitney U test, we tested for significant differences in the identified factors between treatment and control group. Mediated and moderated mediation analyses explored variables such as gender, occupational role, organization, and work sector. Results indicate a sixfactor structure of emotional intelligence, with significant differences observed between groups in the factor empathy difficulty. Peer group mentoring emerges as an effective method for emotional intelligence development among leaders. The perceived importance of emotional intelligence for one's job position, the organization, and the work sector mediated five of the six factors. The